Mining Conflict Resolution in a Communication Perspective: A Literature Review - Nur Azizah Fitrianti; Andre Noevi Rahmanto; Sudarmo (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research aims to find out how communication patterns and how to resolve conflict from a communication perspective. This research uses a qualitative method with a literature review approach. The results of this study show that there are many companies that seek conflict resolution by looking at communication so that the communication patterns that occur in a conflict cannot be separated from how the case views communication itself. Furthermore, this research can conclude that communication cannot separate the conflict that occurs because in a communication process, there will be the potential for a communication failure to occur. Thus, communication will play an important role in how to resolve the conflict that occurs.